The deductibility of interest expenditure under the Income Tax Act 58 of 1962 - Robinson, Georgina Sarah (Department of Commercial Law, 2023)
Many businesses rely on borrowed money to acquire assets or finance their trading activities. High gearing of this nature can be highly tax effective, provided the interest on the loan is tax-deductible. However, the deductibility of interest payments has given rise to much litigation. This is indicative of the many complexities which arise in the practical application of the legal principles. The purpose of this paper is to critically discuss these legal principles applicable to the deduction of interest expense, contained in the four components of the general deduction formulae in s11 (a) read together s 23(g) of the Income Tax Act 58 of 1962 (from hereon referred to as 'The Act'). Following this discussion of the relevant legal principles, the practical application thereof by the courts will be considered in four commercial contexts. It will become evident from this discussion, that most cases are decided on the basis of the 'in the production of income' requirement; which it is submitted, is partly attributable to the courts avoidance of the capital/revenue question which is particularly difficult to apply to interest expense. The essential difficulty encountered in the application of the 'in the production of income' requirement is an evidentiary one. The test requires that the true purpose of the borrowing must be ascertained through the use of objective criteria; and accordingly the onus of adducing such evidence becomes a crucial factor in determining the deductibility of the interest expense. In this regard, section 82 of The Act burdens the taxpayer who disagrees with SARS' refusal to allow an interest deduction with the onus of proving that he is entitled to such a deduction by virtue of the provisions of s11 (a). It follows thus that where uncertainty prevails such that the probabilities are equal, then the burden will not have been discharged. Given the often awkward application of the of the established legal tests to interest expenditure, together with the 'murky evidentiary waters' in which many taxpayers wade when seeking to secure an interest deduction; the incidence of the onus will in many cases be the determinative factor.